Pelatihan Komunikasi Assertif (Assertive Training) Pelajar SMP IT Insan Mulia Surakarta: Assertive Training SMP IT Insan Mulia Surakarta - Ulfa Fauzia Argestya; Galih Fajar Fadillah; Anni Nurul Hidayati; Dhanu Eko Nugroho (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This community service activity aims to provide an inculcation of an effective communication style, namely assertive communication at SMP IT Insan Mulia Surakarta.Online elearning causes students to have difficulty communicating, especially students of SMP IT Insan Mulia Surakarta. Some students still do not dare to refuse friends to play on the sidelines of study group activities or assignments, do not dare to ask the teacher during the learning process, are passive when they have arguments or ideas in organizational forums at school. If this is left without any preventive measures, it will have an impact on the development of student communication at SMP IT Insan Mulia Surakarta. The purpose of this activity is to provides training on effective communication styles, namely assertive communication. The method used in the delivery of communication styles is to use classical and group methods. This training was held for two days. On the first day of classical training in the form of materials and assignments, while the second day in small groups, namely the practice of assertive communication. The data collection instrument used an open questionnaire and observation. Based on the analysis of the instrument students showed changes in communication, namely students to convey their ideas or openly tell the conditions they are experiencing.